Canadian policy toward Khrushchev's Soviet Union - Glazov, Jamie, 1966-; Université du Québec à Montréal. Centre d'études des politiques étrangères et de sécurité.; Teleglobe Raoul-Dandurand Chair of Strategic and Diplomatic Studies (Montreal, Que. : McGill-Queen's University Press, 2002)
"Based on extensive access to previously closed files in the National Archives of Canada, Canadian Policy toward Khrushchev's Soviet Union is the first comprehensive account of Canada's diplomacy toward the Soviet union in the immediate post-Stalin era. Jamie Glazov reveals that the approach taken by the Liberal government of Louis St Laurent (1953-57) was a remarkable achievement for Canadian foreign policy." "Glazov details how the St Laurent government backed the shrewd calculations of the Department of External Affairs and emphasized the wisdom of the containment-accommodation approach, an approach that, he claims, would help win the Cold War thirty-five years later. Glazov shows that the strategy of accommodation, the main difference between Canadian and American Soviet policy, was ultimately vindicated by the eventual ascendancy of a liberal Soviet leader (Gorbachev), which led to increased East-West contact and Soviet liberalization, phenomena that led directly to the West's victory in the Cold War." "Glazov's new assessment of Western policies toward Khrushchev's Russia is critical to our understanding of present-day Russia, since Gorbachev's democratization, which led to the disintegration of the Soviet Union in 1991, had its origins in the Khrushchev thaw. Canadian Policy toward Khrushchev's Soviet Union provides vital information to help answer the question of how the West should deal with Russia, especially in the context of globalization - one of the most urgent issues facing Canada and the Western world."--Jacket
Candian Soviet policy, 1917-1953 -- Canada and de-Stalinization, 1953-1956 -- Tension, raised hopes, and re-Stalinization, 1956-1957 -- Getting tough with the Soviets: John Diefenbaker, 1957-1961 -- The unravelling: conflicts of interest in Diefenbaker's policy after 1961 -- Talking tough without action: the fall of John Diefenbaker, October 1962-1963.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Cold War; Canada -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- Canada; Canada -- Foreign relations -- 1945-; Guerre froide; Canada -- Relations extérieures -- URSS; URSS -- Relations extérieures -- Canada; Canada -- Relations extérieures -- 1945-; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; HISTORY -- Canada -- General; Diplomatic relations; Canada; Soviet Union; Buitenlandse politiek; Koude Oorlog; Canada -- Relations extérieures -- URSS -- 1945-1990.; URSS -- Relations extérieures -- Canada -- 1945-1990.; Guerre froide; Canada -- Relations extérieures -- URSS; URSS -- Relations extérieures -- Canada; Canada -- Relations extérieures -- 1945-; Since 1945